Dermatofibrosarcoma protuberans with a novel COL6A3‐PDGFD fusion gene and apparent predilection for breast. Issue 9 (14th August 2018) - Dickson, Brendan C.; Hornick, Jason L.; Fletcher, Christopher D. M.; Demicco, Elizabeth G.; Howarth, David J.; Swanson, David; Zhang, Lei; Sung, Yun‐Shao; Antonescu, Cristina R.
Abstract: Dermatofibrosarcoma protuberans is a locally aggressive superficial mesenchymal neoplasm. It typically occurs in adulthood, and has been reported to have a slight male predilection. Tumors have a characteristic histopathologic appearance, including: storiform architecture, infiltrative "honeycomb" growth within subcutaneous adipose tissue, and immunoreactivity for CD34. Virtually all molecularly characterized cases to date have been found to harbor a COL1A1‐PDGFB fusion product. Following identification of an index patient with a novel COL6A3‐PDGFD fusion gene, we undertook a molecular investigation, using a combination of RNA sequencing and fluorescence in situ hybridization (FISH), to assess the prevalence of PDGFD rearrangement in dermatofibrosarcoma protuberans (N = 63). Three additional patients were found to have balanced PDGFD rearrangements. Interestingly, all 4 tumors arose on the breast of females. As a result, we subsequently examined 16 additional cases of primary breast dermatofibrosarcoma protuberans, identifying 2 additional tumors with PDGFD rearrangement. The morphology and immunophenotype of all 6 cases was analogous to those with the canonical COL1A1‐PDGFB fusion; none of the cases showed fibrosarcomatous transformation. This study illustrates that the COL6A3‐PDGFD fusion product is rare in dermatofibrosarcoma protuberans, and associated with an apparent predilection for breast. An awareness of this variant is important for pathologists, as it will not be detected using conventional reverse transcription polymerase chain reaction or FISH‐based diagnostic assays for dermatofibrosarcoma protuberans.